2014
DOI: 10.1167/iovs.14-14133
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing c-Cbl Enhances EGFR-Dependent Corneal Epithelial Homeostasis

Abstract: Manipulating the duration of EGFR activity can enhance the rate of restoration of the corneal epithelial layer. Based on our findings, c-Cbl is a new therapeutic target to enhance EGFR-mediated corneal epithelial homeostasis that bypasses the limitations of previous approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The effect on EGF-induced cell migration was verified by suppression of HDAC6 activity by trichostatin A or of its expression by siRNA (Wang et al, 2010a). Extending the duration of EGFR activity by inhibiting its negative regulator, E3 ubiquitin ligase (c-CbI), enhanced the rate of restoration of the corneal epithelial layer both in vitro and in vivo (Rush et al, 2014). In vivo studies in rats with type 1 diabetes mellitus (DM1) showed that a significant delay in corneal epithelial wound healing was correlated with altered EGFR signaling pathways through phosphatidylinositol 3-kinase (PI3K)–Akt and ERK, as well as their downstream BAD signaling pathways in migratory epithelium (Xu and Yu, 2011).…”
Section: Corneal Epithelial Wound Healingmentioning
confidence: 99%
“…The effect on EGF-induced cell migration was verified by suppression of HDAC6 activity by trichostatin A or of its expression by siRNA (Wang et al, 2010a). Extending the duration of EGFR activity by inhibiting its negative regulator, E3 ubiquitin ligase (c-CbI), enhanced the rate of restoration of the corneal epithelial layer both in vitro and in vivo (Rush et al, 2014). In vivo studies in rats with type 1 diabetes mellitus (DM1) showed that a significant delay in corneal epithelial wound healing was correlated with altered EGFR signaling pathways through phosphatidylinositol 3-kinase (PI3K)–Akt and ERK, as well as their downstream BAD signaling pathways in migratory epithelium (Xu and Yu, 2011).…”
Section: Corneal Epithelial Wound Healingmentioning
confidence: 99%
“…The molecular mechanisms that regulate the magnitude, duration, and specificity of EGFR⅐ effector communication are less understood, but these factors determine receptor specific cell biology such as cell proliferation, migration, and differentiation. Further, alterations in regulatory mechanisms are associated with cell transformation (6) and have been targeted to promote receptor activity to enhance wound healing (7).…”
mentioning
confidence: 99%
“…Due to technical limitations, previous in vivo studies have only provided indirect evidence that antagonizing ubiquitylation will promote corneal epithelial wound healing and homeostasis 39 . However, this study provides direct evidence that the inhibition of c‐Cbl can prevent EGFR desensitization as indicated by the slowed rate of EGFR degradation and sustained receptor phosphorylation.…”
Section: Discussionmentioning
confidence: 79%
“…For these compounds to be successful therapeutic agents, it is important to understand the substrate specificity, what stages of membrane trafficking are impacted, and how cell‐biology is affected. Although the inhibition of EGFR ubiquitylation in corneal epithelial cells has been shown to enhance tissue regeneration, 39 this study in corneal epithelial cells is the first to define the contribution of c‐Cbl in controlling EGFR endocytic trafficking and signaling. We are now positioned to study the biological consequences using in vitro (cell proliferation, migration, viability) and in vivo (corneal epithelial development and wound healing).…”
Section: Discussionmentioning
confidence: 97%